2014
DOI: 10.3892/mmr.2014.2172
|View full text |Cite
|
Sign up to set email alerts
|

miR-376b-5p regulates angiogenesis in cerebral ischemia

Abstract: Abstract. The profile of microRNAs (miRNAs) altered following middle cerebral artery occlusion (MCAO) and miRNAs are involved in angiogenesis following cerebral ischemia. miR-376b-5p was decreased following MCAO, however, whether miR-376b-5p is important in angiogenesis remains to be elucidated. The present study was designed to identify whether miR-376b-5p is involved in angiogenesis following cerebral ischemia and to elucidate the underlying mechanisms. A rat MCAO model was established and quantitative polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 37 publications
(31 reference statements)
1
26
0
Order By: Relevance
“…1). A similar study indicated the role of miR-376b-5p in regulating the HIF-1α-mediated vascular endothelial growth factor (VEGF)/Notch1 signaling pathway following permanent MCAO in rats (Li et al, 2014a) (Fig. 1).…”
Section: Micrornas and Post-stroke Pathophysiologymentioning
confidence: 75%
“…1). A similar study indicated the role of miR-376b-5p in regulating the HIF-1α-mediated vascular endothelial growth factor (VEGF)/Notch1 signaling pathway following permanent MCAO in rats (Li et al, 2014a) (Fig. 1).…”
Section: Micrornas and Post-stroke Pathophysiologymentioning
confidence: 75%
“…miR‐376b plays major roles in regulating of various biology activities including cancer, liver regeneration, angiogenesis and cardioprotection . Although no reports revealed the roles of miR‐376b in cardiac diseases, the present study showed miR‐376b‐3p participates in regulation cardiac hypertrophy by inhibiting mitochondrial fission in NRVCs.…”
Section: Discussionmentioning
confidence: 50%
“…Of note, there were no differences in the expression levels of miR ‐ 376b , which is a microRNA associated with various physiological processes including inflammation, (An et al, 2017; Li et al, 2014; Lu et al, 2015) across any brain region, suggesting that the observed reductions in miR‐155 and miR‐146a are not a consequence of a non‐specific reduction in miRNA biogenesis (Fig. 1).…”
Section: Resultsmentioning
confidence: 97%